THE RELATIONSHIP BETWEEN FORMULA MILK CONSUMPTION AND THE SEVERITY OF CARIES IN PRESCHOOL-AGED CHILDREN AT TK AISYIYAH BUSTANUL ATHFAL 42 SEMARANG - Tegar Pramudita; Machmudah Machmudah; Arimbi Arimbi (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: The most common dental and oral disease in children is dental caries. The high prevalence rate of caries, which reaches 81.5% in children aged 3-4 years, is still a problem for Indonesia. One of the causes of the high incidence of caries in preschool children is improper breastfeeding or formula-feeding patterns. This research aims to analyze the relationship between formula milk consumption and the severity of caries in preschool children at TK Aisyiyah Bustanul Athfal 42 Semarang. Method: This study employs an observational-analytical design, specifically a cross-sectional approach. The population of this study were 71 children from Aisyiyah Bustanul Athfal 42 Kindergarten, Semarang.The sample in this study was 66 children. The research sample consisted of 66 respondents selected using a total sampling technique. Data were obtained from dental examinations using the deft index and questionnaires completed by parents/guardians. The data were analyzed using the chi-square test. Results: The study shows that the length, duration, and frequency of formula milk consumption, the use of bottles/pacifiers, the duration of teat/bottle use, the addition of sweeteners to formula milk, as well as the history of breastfeeding until the age of 2 years and the age at which formula milk was first consumed, all show a p-value <0.05, indicating a significant relationship with caries severity. Conclusion: there is a relationship between formula milk consumption patterns and the severity of caries in preschool children at TK Aisyiyah Bustanul Athfal 42 Semarang